KINERJA BALAI PELAYANAN PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (BP3TKI) PEKANBARU (Studi Kasus Pelayanan Penyiapan Dan Penempatan Pekerja Migran Indonesia) - Tya Shafira; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Not achieving the placement of PMI candidates and the number of PMI candidates who process outside the Pekanbaru BP3TKI working area is a phenomenon that is found. The purpose of this study is to find out how the performance of the Indonesian Workers Placement and Protection Service Center (BP3TKI) Pekanbaru in the preparation and placement service and to determine the inhibiting performance of the Indonesian Workers Placement and Protection Service Center (BP3TKI) Pekanbaru. This type of research is a qualitative research with a descriptive approach. Collecting data obtained both primary and secondary data collected through interviews, observations and documentation and then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the performance of the Indonesian Workers Placement and Protection Service Center (BP3TKI) Pekanbaru had not been carried out to the maximum, it was caused by an inhibiting factor namely the lack of infrastructure.  Keywords: Performance, Service, Indonesian Migrant Workers